ASAS AKAD EKONOMI ISLAM PERSPEKTIF KHES (KOMPILASI HUKUM EKONOMI SYARIAH) - Effendi, Bahtiar (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The Compilation of Sharia Economic Law is a legal product that was compiled in response to developments in the study and practice of muamalat law in Indonesia. KHES consists of four book parts, the first book discusses the Subject of Law and Amwal which consists of 3 chapters and 19 articles, the second book discusses the Agreement which consists of 29 chapters with 655 articles. The third book discusses zakat and grants which consists of 4 chapters with 60 articles and the fourth book on Sharia Accounting which consists of 7 chapters with 62 articles. This article was compiled using a qualitative descriptive method to explain the 13 principles in KHES. The principles of the contract include ikhtiyari, amanah, ikhtiyati, luzum, mutual benefit, taswiyah, transparency, ability, taisir (ease), good faith, halal cause, al hurriyah (freedom of contract) and al kitabah (written). Of these thirteen principles, all of them are intended so that every contract that occurs in the economic sphere can run according to sharia, can bring benefits and avoid all forms of omnipresence.